Site analysis : a contextual approach to sustainable land planning and site design - LaGro, James A. (Hoboken, N.J. : John Wiley & Sons, 2008)
"Context-sensitive site planning leads to better development proposals and, ultimately, to higher quality built environments. By responding to inherent site opportunities and constraints, context-sensitive development - and redevelopment - creates attractive and pedestrian-friendly places to live, work, and play." "The expanded and extensively revised new edition, Site Analysis: A Contextual Approach to Sustainable Land Planning and Site Design retains the earlier edition's emphasis on the site-planning process. With several project case studies from leading design firms and more than 180 illustrations, the Second Edition reflects the state of the art in sustainable land planning and site design." "Whether you are a student, a practitioner studying for a licensing exam, or a member of a local board or commission that reviews land development proposals, Site Analysis: A Contextual Approach to Sustainable Land Planning and Site Design will help you better understand the linkages between existing site and contextual conditions - and the sustainable design of the built environment."--BOOK JACKET.
First ed. published 2001.
Keywords: Building sites -- Planning; Building sites -- Environmental aspects; Land use -- Planning; Land use -- Environmental aspects